Adsorptive granulocyte/monocyte apheresis use in severe ulcerative colitis and determination of changes in plasma cytokines. Issue 1 (9th May 2017) - Beltrán, Belén; Sáez‐González, Esteban; Moret, Inés; Díaz‐Jaime, Francia C.; Alvarez‐Sotomayor, Diego; Cerrillo, Elena; Iborra, Marisa; Bastida, Guillermo; Aguas, Mariam; Nos, Pilar
Abstract: Despite controversy regarding the use of granulocyte/monocyte adsorption (GMA) in inflammatory bowel disease, some studies have shown favorable outcomes when it is used in steroid‐dependent patients with ulcerative colitis (UC). The mechanisms responsible for such outcomes are not well characterized, but changes in immune cell populations and cytokine levels have been suggested to play an important role. We report the cases of 3 patients with chronically active severe UC who underwent GMA due to an inadequate response to standard and rescue therapy, as well as changes to their plasma cytokine profile. All the patients presented severe UC that was only partially responsive to various immunosuppressive drugs, and they were, therefore, referred for colectomy; however, all 3 refused this option, which led to the compassionate use of GMA as a last therapeutic resort. Following GMA treatment, rapid normalization of the clinical, endoscopic and laboratory parameters was observed in all the patients. Despite having achieved a good response, most cytokines remained at high concentrations after GMA, and only two, IL‐6 and IL‐8, showed a clear decrease throughout the GMA sessions. In view of this outcome, we hypothesize that GMA can help to lower the inflammatory load, thereby enhancing the effect of biologic drugs. To confirm this hypothesis and explore further indications for GMA, we propose the need for research directed toward the characterization of immune cell populations and their specific cytokine production rather than global cytokine assessment.